What Mum Taught Us Valuable Lessons and Outstanding Hospitality, Including Precious Mesopotamian Recipes - Issa, Theodora (2019)
This book would not have been possible without the existence of that brilliant, vivid, bright, superb, wonderful, luminous, radiant, and very beautiful person whom the authors simply refer to as Mum, or in their Aramaic (Syriac) language, ...